The Role of RDW in Mortality Rates of Stroke Patients - Huseyin BUYUKGOL; Fatma Aysen EREN (Modern Medicine)
Aim: In this study, we examined the relationship between red cell distribution width (RDW) and mortality rates of the stroke patients during the input and the output of the intensive care unit (ICU). Furthermore, we aimed to show the association between RDW levels and the prognosis of the disease. Materials And Methods: Our study was retrospectively performed with 150 stroke patients who were followed in ICU between 01.01.2015 – 31.12.2015. The age, gender, vital parameters, GSK, NIHSS, comorbid diseases, RDW levels in the input and output of ICU, duration of their ICU stays, and mortality rates were examined. Results: Among all participants, 46% of them were male and the age median value was 76 years. There was no relationship between RDW values of participants (p>0.05) and RDW levels of excitus patients during the output from the ICU were significantly higher (p<0.05). In our study, we did not detect a significant difference between RDW levels of all patients and survivors (p>0.05). However, RDW levels of excites patients were signifi cantly higher (p<0.05). RDWinput and RDWoutput levels had negative correlation with GSK and positive correlation with NIHSS (p<0.05). There was a positive correlation between RDWoutput levels and the duration of the hospital stay (p<0.05). Discussion: Consequently, RDW levels in stroke patients are indicators of ischemia or mortality. Furthermore, it seems that RDW levels can also be used as a parameter in the prognosis.